'Better in stereo': Doubled and divided representations of postfeminist girlhood on the Disney Channel. Issue 2 (1st June 2018) - Beail, Linda; Lupo, Lindsey; Beail, Caroline
Disney's cable channel has global reach and the highest audience share among 9–14 year olds, demonstrating its powerful influence in constructing narratives for young citizens. It has produced several films and television shows aimed at tween girls, which embody the paradoxes and 'double entanglements' of postfeminism discussed by Angela McRobbie. These representations demonstrate many postfeminist characteristics, such as a focus on girls' empowerment and neoliberal agency; temporal anxiety and time travel; commodification of racial difference; affluence and consumerism; the assumption of gender equality, even as its achievement makes it politically irrelevant; and femininity/romance as girls' free and natural choice. This paper examines current Disney Channel hits such as Liv and Maddie, Girl Meets World, K.C. Undercover, Teen Beach Movie and Teen Beach 2. The doubling of female identity – following the Hannah Montana pattern of a double life, and replicated in K.C. Undercover and the Teen Beach movies by creating past/present dyads of characters from the 1960s/1970s and the present day – creates the opportunity to represent contrasting ideas of femininity and feminist history, engaging a politics of nostalgia that erases feminism as a political movement, while reaffirming a neoliberal notion of postfeminist girlhood.